Модель зернистого композита со сферическими зернами - Николаев, А. Г.; Танчик, Е. А. (НТУ "ХПИ", 2014)
Предложена модель зернистого композита, в которой зерна моделируются упругими сферическими включениями. Напряженное состояние в композите описывается краевой задачей для уравнения Ламе с условиями идеального контакта на границе зерен и условиями на бесконечности. Аналитическое решение строится в виде суперпозиции точных базисных решений уравнения Ламе в сферических системах координат, начала которых отнесены к центрам включений. Граничные условия удовлетворяются точно при помощи обобщенного метода Фурье. Задача сведена к бесконечной системе линейных алгебраических уравнений с фредгольмовым оператором. Приведен численный анализ нормальных компонент тензора напряжений в области между включениями.

A model of granular composite, in which the grains are modeled by elastic spherical inclusions, is proposed. The stress state in the composite is described by a boundary value problem for Lame’s equation with ideal contact conditions at the grain boundaries and conditions at the infinity. The analytical solution is constructed as a superposition of the exact basis solutions of Lame’s equation in spherical coordinate systems, which origins are related to the centers of inclusions. The boundary conditions are satisfied exactly by using the generalized Fourier method. The problem is reduced to an infinite system of linear algebraic equations with Fredholm operator. The numerical analysis of the normal components of the stress tensor in the region between the inclusions is given.
Model of granular composite with spherical grains
Keywords: обобщенный метод Фурье; метод редукции; уравнение Ламе; система координат; granular composite; spherical inclusions; generalized Fourier method; method of reduction